Diversifikasi Produk Nutrisi Berbahan Dasar Ikan Lele pada Kelompok Nelayan Wanita Kab. Mempawah sebagai Salah Satu Upaya Penanganan Stunting - Fitriagustiani, Fitriagustiani; Pasmawati, Pasmawati; Khairillah, Yuyun Nisaul; Pratama, Sandi Fransisco; Alang, Hasria (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Poor nutritional status of the community leads to weak human development index (HDI) values. Increasing interest in fish consumption, which is rich in diverse nutritional sources, can be a solution to improved people nutritional status in coastal communities whose livelihood marine-dependent. Fish is known as a good source of a high quality protein. This nutritional source plays an important role to provide the nutrition of pregnant women and the development of toddlers. Food diversification by using aquaculture products is expected to be one solution to increased public interest in consuming fish and also could be away to increase the selling value of fishery products. This social service aims to provide information in utilizing the fishery products (i.e Catfish) as a food diversification materials to prevent stunting in the Pak Bulu village community, Anjongan sub-district, Mempawah Regency. The stages of this activity include 1) Survey and analysis of community conditions, 2) Stunting education and introduction to the process of food diversification fish based. This community Service activities are expected to increase knowledge and skills in processing fishery products. Therefore, it can increase fish consumption in the community and become one of the solution to prevent stunting and also could be a way to improve the community's economy.